Structural plasticity of green fluorescent protein to amino acid deletions and fluorescence rescue by folding-enhancing mutations. Issue 1 (December 2015) - Liu, Shu-su; Wei, Xuan; Dong, Xue; Xu, Liang; Liu, Jia; Jiang, Biao
Abstract Background Green fluorescent protein (GFP) and its derivative fluorescent proteins (FPs) are among the most commonly used reporter systems for studying gene expression and protein interaction in biomedical research. Most commercially available FPs have been optimized for their oligomerization state to prevent potential structural constraints that may interfere with the native function of fused proteins. Other approach to reducing structural constraints may include minimizing the structure of GFPs. Previous studies in an enhanced GFP variant (EGFP) identified a series of deletions that can retain GFP fluorescence. In this study, we interrogated the structural plasticity of a UV-optimized GFP variant (GFPUV ) to amino acid deletions, characterized the effects of deletions and explored the feasibility of rescuing the fluorescence of deletion mutants using folding-enhancing mutations. Methods Transposon mutagenesis was used to screen amino acid deletions in GFP that led to fluorescent and nonfluorescent phenotypes. The fluorescent GFP mutants were characterized for their whole-cell fluorescence and fraction soluble. Fluorescent GFP mutants with internal deletions were purified and characterized for their spectral and folding properties. Folding-ehancing mutations were introduced to deletion mutants to rescue their compromised fluorescence. Results We identified twelve amino acid deletions that can retain the fluorescence of GFPUV . Seven of these deletions are either at the N- or C- terminus, while the other five are located at internal helices or strands. Further analysis suggested that the five internal deletions diminished the efficiency of protein folding and chromophore maturation. Protein expression under hypothermic condition or incorporation of folding-enhancing mutations could rescue the compromised fluorescence of deletion mutants. In addition, we generated dual deletion mutants that can retain GFP fluorescence. Conclusion Our results suggested that a "size-minimized" GFP may be developed by iterative incorporation of amino acid deletions, followed by fluorescence rescue with folding-enhancing mutations.